Competitive Excimer Formation and Energy Transfer in Zr‐Based Heterolinker Metal–Organic Frameworks. Issue 37 (12th July 2016) - Gutiérrez, Mario; Sánchez, Félix; Douhal, Abderrazzak
Abstract: The spectroscopy and dynamics of a series of Zr‐based MOFs in dichloromethane suspension are reported. These Zr‐NADC MOFs were constructed by using different mixtures of 2, 6‐naphthalenedicarboxylate (NDC) and 4‐amino‐2, 6‐naphthalenedicarboxylate (NADC) as organic linkers. The fraction of NADC relative to NDC in these heterolinker MOFs ranges from 2 to 35 %. The results indicate two competitive photoprocesses: NDC excimer formation and an energy transfer (ET) from excited NDC linkers to NADC linkers. Increasing the fraction of NADC linkers in the Zr‐NADC nanostructure decreases the mean time constant of NDC excimer formation, while the NADC emission intensity experiences a drop at the highest fraction of this linker in the MOF. The first observation is explained by an increase in the energy‐transfer probability between the two linkers, and the second by emission quenching in the NADC linkers due to ultrafast charge transfer assisted by the amino group. Femtosecond time‐resolved emission studies showed that the ET process (recorded as decaying and rising components) from excited NDC to NADC takes place in 1.2 ps. Direct excitation of the NADC linkers (at 410 nm) shows a decaying, but not rising, component of 250–480 fs, which could reflect the formation of a nonemissive charge‐separation state. The results show that by using MOFs having heterolinkers it is possible to trigger and tune excimer formation and ET processes. Abstract : Competitive links : Two competitive interlinker photoprocesses take place in Zr‐based MOFs with mixtures of 2, 6‐naphthalenedicarboxylate (NDC) and 4‐amino‐2, 6‐naphthalenedicarboxylate (NADC) linkers. In one of them the interaction between adjacent NDC linkers leads to excimer photoformation on a timescale of hundreds of picoseconds, and in the other ultrafast electron transfer from excited NDC linkers to NADC linkers takes place in 1.2 ps (see figure).